2007
DOI: 10.1111/j.1360-0443.2007.02025.x
|View full text |Cite
|
Sign up to set email alerts
|

Risk of fatal overdose during and after specialist drug treatment: the VEdeTTE study, a national multi‐site prospective cohort study

Abstract: We demonstrate that a range of treatments for heroin dependence reduces overdose mortality risk. However, the considerable excess mortality risk in the month following treatment indicates the need for greater health education of drug users and implementation of relapse and overdose death prevention programmes. Further investigation is needed to measure and weigh the potential benefits and harms of short-term therapies for opiate use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
134
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 190 publications
(148 citation statements)
references
References 27 publications
14
134
0
Order By: Relevance
“…The only study we found that examines the risk of premature deaths shortly after leaving treatment used a four-week window (Davoli et al, 2007). In the prison literature, the time window for a high risk of death varies between studies, ranging from one to four weeks or even longer (Ødegård et al, 2009).…”
Section: Definition Of the Time Windowmentioning
confidence: 99%
See 3 more Smart Citations
“…The only study we found that examines the risk of premature deaths shortly after leaving treatment used a four-week window (Davoli et al, 2007). In the prison literature, the time window for a high risk of death varies between studies, ranging from one to four weeks or even longer (Ødegård et al, 2009).…”
Section: Definition Of the Time Windowmentioning
confidence: 99%
“…It is well documented that there is a high mortality rate among drug users, and that death by overdose is common cause of death in that group (Clausen et al, 2008;Darke and Degenhardt, 2007;Davoli et al, 2007;Bargagli et al, 2006;Johnson et al, 2005;Gossop et al, 2002). Actually, deaths from opiate overdose comprise the vast majority of all drugrelated deaths (Strang et al, 2008;Darke and Zador, 1996).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…OST is highly cost‐effective, whether delivered in the community or prison 17, 18, 19. Prolonged OST is associated with improved survival 5; however, recent studies highlight very high mortality risk in the month after treatment cessation 20, 21, 22, 23. There have also been reports of an elevated risk of mortality during the first month of OST 20, 21, 24, 25.…”
Section: Introductionmentioning
confidence: 99%